1998
DOI: 10.1007/s004150050192
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibodies against membranous labyrinth in patients with „idiopathic“ bilateral vestibulopathy

Abstract: To investigate the possibility of an autoimmune mechanism in idiopathic bilateral vestibulopathy (IBV), we screened patients' sera for antibodies against inner ear structures. IgG antibodies against membranous labyrinth (ampulla, semicircular canals, saccule and utricle) were detected in 8 of 12 patients by immunofluorescence on rat inner ear cryosections. All but one serum of 22 healthy controls and the sera of 6 patients with known autoimmune disorders showed only background staining. Low-titre anti-nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Previous reports suggested that the progressive type could be related to autoimmune disease. Arbusow et al [6] reported that antibodies against the membranous labyrinth (including the cochlea) were detected in some IBV patients. They concluded that Matsuzaki/Murofushi only a small subgroup of organ-specific autoantibodies would play a role in the pathogenesis of IBV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports suggested that the progressive type could be related to autoimmune disease. Arbusow et al [6] reported that antibodies against the membranous labyrinth (including the cochlea) were detected in some IBV patients. They concluded that Matsuzaki/Murofushi only a small subgroup of organ-specific autoantibodies would play a role in the pathogenesis of IBV.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to both caloric and rotational tests are markedly decreased bilaterally, but the findings of other neurological examinations are unremarkable. Various etiologies such as viral infection, autoimmune or degenerative disease, and ischemic attack have been proposed for this disorder [1][2][3][4][5][6]. However, 'idiopathic' cases still exist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absent or markedly decreased response of the LSCC is revealed in the caloric test, the rotation test [3,6,26,29,31] and the head thrust test [35,36]. Originally, IBV is not accompanied by cochlear or any other neurological symptoms [6].…”
Section: Introductionmentioning
confidence: 97%
“…We presume that anti-labyrinthine antibodies represented an epiphenomenon of a cellular autoimmune process [2]. The sudden onset of the disease in our patient and its amelioration under anti-inflammatory and immunosuppressive treatment as well as the appearance of anti-labyrinthine antibodies were indications to us of an autoimmune origin.…”
Section: Discussionmentioning
confidence: 91%